2005
DOI: 10.1016/j.landurbplan.2004.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Community and landscape change in southeast Alaska

Abstract: Since the early 1970s, social science research has addressed issues concerning the nature and distribution of values and uses associated with natural resources. In part, this research has tried to improve our understanding of interconnections between resource management and social and cultural change on the Tongass National Forest in southeast Alaska. In 1997, scientists at the Pacific Northwest Research Station (PNW) initiated a number of social science studies in response to information gaps identified while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…27-8) as some patterns of landscape evaluation are clear and broadly consistent with other forest landscape evaluation and social acceptability studies (Kruger, 2005). For instance, participant comments demonstrated that multiple factors are brought to bear in the evaluation of alternative landscape conditions.…”
Section: Discussion: Implications For Landscape Planning and Researchsupporting
confidence: 61%
See 2 more Smart Citations
“…27-8) as some patterns of landscape evaluation are clear and broadly consistent with other forest landscape evaluation and social acceptability studies (Kruger, 2005). For instance, participant comments demonstrated that multiple factors are brought to bear in the evaluation of alternative landscape conditions.…”
Section: Discussion: Implications For Landscape Planning and Researchsupporting
confidence: 61%
“…Consistent with the broader field of social acceptability research (Kruger, 2005;Stankey, 1996;Schindler et al, 2002), participant appraisals addressed the perceived balance of impacts associated with the different landscape conditions. In effect, the participants engaged in a complex evaluation of multiple consequences when evaluating the simulated conditions.…”
Section: Balance Of Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with perception research in human geography (Hay 1998;Kruger 2005;Shindler et al 2002), participants associated multiple values with their environment and made complex evaluations of multiple impacts of change to specific ES. It was difficult to gauge whether the participants carried out multicriterion analysis.…”
Section: Resultsmentioning
confidence: 76%
“…In many cases of community tourism development, the elite become the main beneficiaries while few of the local residents participate or gain much profit from tourism (Pratiwi 2000). The results of Kruger's (2005) survey of the effects of tourism on three communities in Southeast Alaska proved that although the tourism industry can be 'the goose that lays the golden egg', it can also be a way of 'fouling one's own nest'. Campbell (1999) found that local community residents in Costa Rica gained limited benefits from tourism if they lacked knowledge about tourism development and if there was a lack of government planning and participation in the process.…”
Section: Introductionmentioning
confidence: 99%